Incidência de conduta violenta e antissocial em população psiquiátrica forense - Borba Telles, Lisieux Elaine de (2011)
Introduction: The consequences of violent and antisocial behaviors among psychiatric hospital inpatients are serious and may affect treatment of the aggressor. Lack of knowledge concerning the incidence of this phenomenon and its characteristics helps perpetuate the current scenario. Objectives: To present an up-to-date literature review on the topic, to estimate the incidence of violent and antisocial behaviors in a mental hospital population, and to describe the implementation of a systematic method to record this phenomenon. Method: A cohort was selected among the psychiatric inpatients at Maurício Cardoso Forensic Psychiatry Institute (Instituto Psiquiátrico Forense Maurício Cardoso, IPFMC). Yudofsky's Overt Aggression Scale (OAS) and Tengström et al.'s Follow-Up Questionnaire were used. During a 1-year follow-up period, episodes of violent and antisocial behavior were evaluated daily and recorded on both the scale and the questionnaire. The population sample included 68 male patients randomly selected among the committed inpatients at IPFMC. Results: The incidence of violent/antisocial behavior along the period assessed was 200 episodes involving 50 patients. Aggressions and antisocial behavior occurred mainly in daytime. The interventions most commonly used were verbal management, patient isolation, and intramuscular medication. Conclusion: For the first time, the occurrence of violent and antisocial behavior was measured in a forensic psychiatric population.